Subliminal Interdependence Priming Modulates Congruent and Incongruent Facial Reactions to Emotional Displays - Seibt, B. (2014)
To investigate how facial reactions to facial emotional displays are modu- lated by cues about social interdependence processed outside of aware- ness, 84 women were subliminally primed with cooperation or competi- tion or neutrally primed. Thereafter, they viewed computer-generated faces with happy, neutral, sad, and angry expressions while facial EMG was recorded over three muscles. As expected, we observed congruent facial reactions in the neutral and cooperation conditions to happy and sad but not to angry faces. In the competition condition, we found almost no con- gruent reactions. Furthermore, we observed incongruent reactions to angry expressions: participants primed with competition and participants primed with cooperation showed positive reactions, but on different muscles. We argue that these incongruent reactions are based on reward contingencies and on habitual communicative goals to support a partner, respectively.